Chronic kidney disease stages 3-5 in iranian children: Need for a school-based screening strategy: The caspian-iii study - Alaleh Gheissari (International Journal of Preventive Medicine, 2013)
Background: There is scarce epidemiological data on early and asymptomatic stages of chronic kidney disease (CKD) in children, especially from developing countries. In this study, we investigated the frequency of CKD stages 3-5 among general students of Isfahan (a large province of Iran), and compared the findings with those derived from the main pediatric nephrology referral center of province. Methods: This study was performed among 712 Isfahani school students (377 boys) aged 7-18 years, as part of the baseline survey of a national surveillance system. Blood samples were analyzed for blood urea nitrogen, creatinine, and cystatin C. Glomerular filtration rate (GFR) was calculated based on two 2009 Schwartz equations (the "updated" and the "new" equations). CKD was defined as GFR <60 ml/min/1.73 m 2 . Additionally, a retrospective analysis of clinical records of children with stages 3-5 CKD referred to main referral center of province from November 2001 to December 2011 was made. Results: The mean age of students was 12.2 ΁ 2.4 years. In students′ screening, the frequency of CKD was 1.3% and 1.7% based on the updated Schwartz and the new Schwartz equation, respectively. The referral center survey revealed an annual incidence of 14.5 per million age-related population (pmarp), and a prevalence of 118.8 pmarp in our province. Conclusion: The prevalence of asymptomatic and undetected low GFR in Iranian children is higher than what is reflected from the reports of referral centers. Simple screening programs like annual urinalysis among high-risk school students should be considered.